Inovasi UMKM Gable BOX Melalui Strategi Penggunaan E-Commerce untuk Meningkatkan Income Panti Asuhan Aisyiyah - Dewi, Ika Parma; Sisi, Mardiana Putri; Nofelia, Nofrianti; Nadila, Lativa; Zuhro, Kyranty Putri; Tuazmi, Noferli; Arrahman, Mufhadil; Alfadly, Israd Muhammad; Aprilianda, Olga; Ceria, Putri Rio (Institut Riset dan Publikasi Indonesia (IRPI), 2025)
Orphanages play an important role in providing protection and guidance for orphans and the poor, including through the development of life skills that support their independence in the future. Aisyiyah Koto Tangah Padang Orphanage faces challenges in operational sustainability due to limited financial resources. This article discusses the innovation of developing MSMEs based on Gable Box production as an effort to empower the economy of orphanages. Through training in making Gable Boxes, bracelet products, and digital marketing by utilizing social media, this activity aims to improve the skills of orphanage children in entrepreneurship and digital technology. The methods used include observation, direct training, and documentation. The results of the training show that orphanage children have high interest and potential in the creative field, but previously did not have a place to develop these abilities. This initiative is the first step towards sustainable economic empowerment and increasing digital capacity in the orphanage environment.